2010
DOI: 10.3109/01902140903131200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myristoylated alanine-rich C kinase substrate (MARCKS) protein inhibits ozone-induced airway neutrophilia and inflammation

Abstract: Evidence suggests inhibition of leukocyte trafficking mitigates, in part, ozone-induced inflammation. In the present study, the authors postulated that inhibition of myristoylated alanine-rich C kinase substrate (MARCKS), an 82-kDa protein with multiple biological roles, could inhibit ozone-induced leukocyte trafficking and cytokine secretions. BALB/c mice (n = 5/cohort) were exposed to ozone (100 ppb) or forced air (FA) for 4 hours. MARCKS-inhibiting peptides, MANS, BIO-11000, BIO-11006, or scrambled control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Moreover, the finding that the MANS peptide is effective in attenuating MARCKS function, as opposed to the missense RNS peptide, precludes the nonspecific peptide effects that might occur with a more generalized inhibitor. Thus, our data affirm that interference with MARCKS function markedly reduces cytokine secretion, and extends the role of MARCKS protein beyond neutrophil degranulation (21) and adhesion/migration (3,4,29) into cytokine production and the regulation of mRNA transcript synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, the finding that the MANS peptide is effective in attenuating MARCKS function, as opposed to the missense RNS peptide, precludes the nonspecific peptide effects that might occur with a more generalized inhibitor. Thus, our data affirm that interference with MARCKS function markedly reduces cytokine secretion, and extends the role of MARCKS protein beyond neutrophil degranulation (21) and adhesion/migration (3,4,29) into cytokine production and the regulation of mRNA transcript synthesis.…”
Section: Discussionsupporting
confidence: 75%
“…Since 2005, there have been a number of key experimental animal studies carried out in mice that demonstrated acute inflammation and airway injury following acute (Damera et al, 2010) or sub-chronic exposure (Inoue et al, 2008;Yoon, Cho & Kleeberger, 2007) to environmentally pertinent ozone concentrations in the range 100-300 ppb. Additional subchronic and chronic ozone exposure studies (500 ppb) in rhesus monkeys have demonstrated structural changes in the distal and proximal airways (Fanucchi et al, 2006;Carey et al, 2011) and allergy-like patterns of response (increased globlet cells and eosinophils) to allergen and ozone co-challenges (Kajekar et al, 2007;Miller et al, 2009;van Winkle et al, 2010;Plopper et al, 2007).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…After centrifuging (500 3 g for 10 minutes at 4°C), the cell pellet was resuspended in RPMI medium. Differential cell counts were performed from cytospin preparations, as described elsewhere (15). Cells were identified as macrophages, eosinophils, neutrophils, and lymphocytes according to standard morphology, and a minimum of 300 cells was counted using a Nikon microscopic system (Nikon Instruments, Melville, NY) (3400 magnification).…”
Section: Bal Cell Count and Differential Cell Countmentioning
confidence: 99%